(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Household waste management at the village level remains challenged by low waste segregation practices and limited behavioral change. This study aimed to promote a zero-waste lifestyle through the “Minim Sampah” program in Cimalaka Village, Sumedang Regency. A participatory education approach was applied, involving pre-test and post-test assessments, interactive lectures, focus group discussions, and household-level mentoring of 46 families. Results showed a significant increase in knowledge scores from 40 to 85. Approximately 80% of households adopted waste sorting practices, five composting units were established, and waste volume transported to disposal sites decreased by 10%. These findings indicate that behavior-based interventions integrated with zero-waste principles are effective in promoting independent waste management. This model is recommended for replication in similar rural settings.